Use of a serotype-specific urine immunoassay to determine the course of a hospital outbreak of Streptococcus pneumoniae complicated by influenza A. Issue 1 (12th February 2016) - Sheppard, Carmen L.; Clark, John; Slack, Mary P. E.; Fry, Norman K.; Harrison, Timothy G.
Abstract : Introduction: An outbreak of Streptococcus pneumoniae (pneumococcal) infection complicated by concomitant influenza A on an elderly care ward was detected. Case presentation: Thirteen patients with hospital-acquired respiratory infections were investigated during the course of the outbreak investigation. Six had a positive BinaxNOW S. pneumoniae urinary antigen test and two patients had culture-confirmed pneumococcal bacteraemia and a positive urine antigen test. Five patients gave positive influenza A PCR results of which two were also positive for S. pneumoniae antigen. Conclusion: The concurrence of influenza and pneumococcal infections made tracking the course of the infection difficult. This case study shows how the use of a sensitive, S. pneumoniae serotype-specific urine antigen assay, in the absence of cultured isolates, helped determine whether patients were infected with the same pneumococcal serotype. This was particularly useful when additional respiratory symptoms were seen following the administration of chemoprophylaxis.